In Vitro Evaluation of Manual Torque Values Applied to Implant-Abutment Complex by Different Clinicians and Abutment Screw Loosening - Kose, Onur Dincer; Karatasli, Burcin; Demircan, Sabit; Kose, Taha Emre; Cene, Erhan; Aya, Serhan Aydjn; Erdem, Mehmet Ali; Cankaya, Abdulkadir Burak (HINDAWI LTD, 2017)
Preload is applied to screws manually or using a torque wrench in dental implant systems, and the preload applied must be appropriate for the purpose. The aim of this study was to assess screw loosening and bending/torsional moments applied by clinicians of various specialties following application of manual tightening torque to combinations of implants and abutments. Ten-millimeter implants of 3.7 and 4.1 mm diameters and standard or solid abutments were used. Each group contained five implant-abutment combinations. The control and experimental groups comprised 20 and 160 specimens, respectively. Implants in the experimental group were tightened by dentists of different specialties. Torsional and bending moments during tightening were measured using a strain gauge. Control group and implants with preload values close to the ideal preload were subjected to a dynamic loading test at 150 N, 15 Hz, and 85,000 cycles. The implants that deformed in this test were examined using an optical microscope to assess deformities. Manual tightening did not yield themanufacturer-recommended preload values. Dynamic loading testing suggested early screw loosening/fracture in samples with insufficient preload.
Keywords: FATIGUE PERFORMANCE; COMPLICATION RATES; INTERFACE; SURVIVAL; DESIGN; Biotechnology & Applied Microbiology; Research & Experimental Medicine